Transformational Leadership and Teacher Performance in the Digital Era: A Case Study of an Indonesian Madrasah - Zahwa Rifqotul Maula; Lailatul Hidayah Ayu Putri (Al-Qalam Institue, 2026)
This study aims to examine how transformational leadership is implemented by the head of madrasah to improve teacher performance in the digital era at Madrasah. Digital transformation has reshaped governance, learning practices, and teacher professionalism, requiring leaders to manage technological and cultural change. In madrasah contexts, this issue is important because digital adaptation must align with institutional values, limited resources, and teacher readiness. This research employed a qualitative single-case study design. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show, first, that teacher performance was strengthened through mentoring, supervision, motivation, and evaluation. Second, transformational leadership appeared through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Third, implementation was supported by leadership commitment, collaborative culture, stakeholder support, parental participation, and technology use. However, it was constrained by competence gaps, infrastructure, communication problems, resistance, and unequal readiness. These findings imply that transformational leadership functions as an adaptive mechanism for teacher development. Practically, madrasah leaders should design collaborative and differentiated professional development strategies.